Investigation of Structure and Properties of Barrier Layers in Metals (Fe, Cu) at Low Temperatures - Kuterbekov, K. A.; Nurkenov, S. A.; Kislitsin, S. B.; Kuketayev, T. A.; Tussupbekova, A. K. (Springer US, 2016)
Experimental studies of the effect of a barrier layer on the kinetics of thermally induced diffusion procesess and phase transformations in a layered Fe–Be syatem are investigated at the energy ~1.6 MeV. Thermal stability of the barrier layer in the Fe:O+ system is validated and a possibility of its use as a subsurface layer for a beryllium coating is demonstrated. For the Cu:O+ system it is shown that the implanted layer in the matrix comes apart already at the annealing temperature ~180°C and could not be used in a copper matrix as a subsurface barrier layer. For the first time, a method is proposed for retardation of diffusion and phase formation processes and realized in a layered iron – beryllium system using an implanted layer of oxygen ions. The sequence and characteristic times of thermally-induced phase-transformation processes taking place in the subsurface layers and in the bulk of the Fe (10 μm) systems: O+ – Be (0.7 μm) – 57Fe (0.1 μm) and Fe (10 μm) – Be (0.7 μm) – 57Fe (0.1 μm) are determined.
Keywords: oxygen ion implantation; barrier layer; thermal stability; phase transformations